Mengembangkan Kebugaran Fisik Dengan Mengadakan Pelatihan Sepak Bola Di Desa Ciklapa Tahun 2023 - Kuat Leksono; Dwi Septian; Andhika Hidayat Kurniawan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Thematic KKN contains a series of interdisciplinary integrative activities which are packaged strategically to solve problems which are carried out together with the community by playing the community as the main actor and involving other related stakeholders. In this case, students act as motivators in the process of solving problems and building or developing society. The work program that has been prepared is football training. In the soccer training work program, the objects are children around the post and several hamlets. Football training is carried out 4 times in 4 weeks